Effects of total urethral suspension combined with posterior pelvic floor reconstruction on sexual function in women with stress urinary incontinence and concomitant vaginal laxity syndrome - Li, Yuan; Shen, Jihong; Li, Ling; Tian, Daoming; Wen, Yubin; Li, Hongcheng; Gu, Jiangna; Luo, Qian; Gao, Zhenhua; Wang, Xingqi (Frontiers in Surgery, 2025)
ObjectiveTo assess the impact of total urethral suspension with posterior pelvic floor reconstruction on sexual function in women with stress urinary incontinence(SUI) and concomitant vaginal laxity syndrome (VLS), including partner satisfaction.MethodsClinical data from 150 pelvic floor dysfunction patients were collected at the First Affiliated Hospital of Kunming Medical University (March 2023–March 2024). Preoperative assessments included demographics, obstetric/surgical history, menopausal status, sexual activity and maximum levator hiatal area during Valsalva maneuver on ultrasound. Seventy-five sexually active patients completed the Pelvic Organ Prolapse/Urinary Incontinent Sexual Function Questionnaire Short Form (PISQ-12), with partner satisfaction and vaginal tightness evaluations. At the 1-year postoperative follow-up, patients underwent outpatient clinical evaluations, including the PISQ-12 questionnaire, assessments of vaginal tightness and partner satisfaction, and pelvic floor ultrasound measurements.ResultsThe subjective cure rate for urinary incontinence was 86.67% with a 10.67% improvement rate. Significant improvements were observed in PISQ-12 scores (preoperative: 17.56 ± 5.56 vs. postoperative: 11.72 ± 4.23; P < 0.01). Partners reported increased overall satisfaction (3.21 ± 0.92–3.81 ± 1.06; P < 0.01) and enhanced perception of vaginal tightness (2.47 ± 0.58–4.17 ± 0.62; P < 0.01).ConclusionThe combined surgical procedure demonstrates significant therapeutic efficacy in managing SUI and concomitant VLS, with postoperative outcomes showing substantial improvements in both urinary continence and sexual function. Total urethral suspension provides comprehensive to treat SUI. Posterior pelvic floor reconstruction restores anatomical integrity by reducing the levator hiatus and reconstructing the perineal body, thereby normalizing vaginal axis alignment. The subsequent vaginal tightening achieved through these procedures significantly enhances sexual function for both patients and their partners.